Numerical simulation of foaming processes - Gladbach, Katharina; Delgado, Antonio; Rauh, Cornelia (World Journal of Mechanics, 2017)
The literature model studied in this article describes bubble formation and growth in a highly viscous polymer liquid with support of a gaseous matter dispersed under pressure before foaming. The foam growth is induced by the application of vacuum and mass transport of volatile components dissolved in the polymer liquid. Based on this literature model, aeration processes are calculated for intermediate viscosity and low viscosity biological systems, as they are of interest for biomatter foams, in particular for food foams in industrial processes. At the end of this article, the numerical results are presented and discusse
Keywords: Foaming Process; Conservation Equations; Finite Difference Method; Convergence Analysis; Reynolds Number; Newtonian Liquids